Evaluation Analysis of Free Nutritious Meal (MBG) Program: Case Study of SD Negeri 3 Bukit Tunggal, Palangka Raya - Nurul Hikmah; Adithiya Wiradinatha Saputra; Novrel Esa Yubel; Ridha Ramadhany; Pambajeng Luluh Dyah Pangestu; Rio Pratama; Chrismantya Dwi S N; Ivan Borneva; Murraya Putri Palupi; Intan Kumalasari (Poltanesa, 2025)
Improving the quality of public health is a national priority, one of which is through the Free Nutritious Meal (MBG) program launched by President Prabowo. However, the emergence of cases of MBG poisoning in several areas, including Palangkaraya, confirms the need for a more in-depth evaluation of program governance. Studies on MBG with William N. Dunn's evaluation approach are still limited, six indicators of Dunn's evaluation. This study uses a descriptive qualitative case study method through observation, interviews, and documentation of 10 informants consisting of teachers, students, guardians, and SPPG. Analysis using Nvivo 12 was conducted to identify patterns, barriers, and opportunities for improvement. The results show that the structure of target groups and beneficiaries indicates that the implementation of MBG is not linear, but interdependent, where the success of each actor depends on the contribution of other actors in the policy chain. The most dominant dimension of the causal mechanism is the readiness of inputs, especially adequate human resources. However, strengthening the aspects of funding (activities), logistics and volunteer work intensity (outputs), menu variations (outcomes), and feedback mechanisms are still needed (impact). These findings affirm the importance of continuous coordination between actors to ensure the sustainability and effectiveness of MBG as a strategic instrument in improving the quality of human resources since elementary school.